Pembinaan Akhlak Siswa Oleh Guru Pendidikan Agama Islam Di SMP Negeri 10 Lebong - Suryono, Suryono; Amda, Ahmad Dibul; Sutarto, Sutarto (Jurnal Ilmiah Mandala Education (JIME), 2021)
This study aims to describe the efforts to develop students' morals by PAI teachers at SMP Negeri 10 Lebong in addition to knowing what obstacles were found in efforts to foster students' morals by PAI teachers at SMP Negeri 10 Lebong. This research is expected to make a scientific contribution to the development of science, especially PAI and Student Moral Development in schools. This research is a research (field research) and the use of a qualitative descriptive approach. The data and sources of data in this study are Islamic religious education teachers and school principals. Data collection techniques using observation, interviews and documentation. The data analysis technique has 3 stages, namely data reduction, data presentation and conclusion drawing. In research the data must be acceptable to support the conclusions of the study. Therefore, it is necessary to use data validity standards consisting of: 1. credibility, 2. transferability, 3. dependability, 4. comfirmability. From the results of the research carried out in this study, it is the moral development of students by PAI teachers through PAI learning at SMP Negeri 10 Lebong, including the habituation method, the exemplary method, the storytelling method and the historical method. In addition, the moral development of students by PAI teachers is also carried out through religious extracurricular activities at SMP Negeri 10 Lebong such as the implementation of congregational and timely prayers, BTQ activities (Read, then through Lectures, Advice and Stories or History stories, as well as monitoring with parents/guardians of students In the implementation of moral development, of course, there are several obstacles including First, the lack of means of communication, the second factor is the lack of good transportation facilities, the third factor is the current Covid-19 pandemic which requires learning processes and extracurricular activities in fostering students' morals carried out by BDR (Learning From Home).